PENGARUH MAJAPAHIT PADA BANGUNAN PURI GEDE KABA-KABA, TABANAN - Susetyo, Sukawati (Penerbit BRIN (BRIN Publishing), 2016)
Abstract. Majapahit Influence on the Grand Palace of Kaba-Kaba, Tabanan. Majapahit, as a kingdom, had spread its influence to almost every part of Indonesia such as the western part of Sumatra and the eastern part of the Moluccas, even to our neighbouring countries in Southeast Asia, which were implemented in form of equal partnership (mitra satata). The archaeological remains from the Majapahit period that we can see include sacred and profane buildings, sculptures, reliefs, fragmented and intact potteries and ceramics, and literatures. They bear distinct characteristics, particularly in sacred buildings as well as the styles of reliefs and sculptures. Kaba-Kaba Palace is theremain of Kaba-Kaba Kingdom in Tabanan, Bali, whose king was originated from Majapahit. The aim of this research is to uncover the Majapahit influence on this palace. Furthermore, an attempt was also made to see whether it was built in accordance with Sanga Mandala, a concept used in the building of palaces. The method for this study was carried out by literature study and describing the building elements of the palace that have Majapahit influence, as well as interviewing some sources. The results show that the palace was built based on the sangamandala concept but it has experienced development to accommodate the needs of more recent period. The Majapahit influences on the Kaba-Kaba Palace are seen in the candi bentar (split gate), paduraksa (roofed gate), tantricstyle sculptures, the sculptures of tortoise and dragon, and figure with the face of a stranger. Keywords: Influence, Majapahit, the Grand Palace of Kaba-Kaba Abstrak. Majapahit sebagai kerajaan besar telah mengembangkan pengaruhnya meliputi hampir di seluruh wilayah Indonesia saat ini, yaitu daerah-daerah di Pulau Sumatra di bagian barat dan Maluku di bagian timur, bahkan pengaruhnya meluas sampai ke negara tetangga di Asia Tenggara yang dijalin dalam bentuk persahabatan yang setara (mitra satata). Tinggalan arkeologi dari masa Majapahit yang dapat kita temui adalah bangunan suci, arca-arca, relief, bangunan profan, fragmen/utuh gerabah dan keramik, dan karya-karya sastra. Tinggalan Majapahit tersebut mempunyai ciriciri khusus dalam bentuk arsitektur bangunan suci, gaya relief dan arca. Puri Kaba-Kaba merupakan tinggalan Kerajaan Kaba-Kaba di Tabanan, yang rajanya berasal dari Majapahit. Tujuan penelitian ini untuk mengetahui apa saja pengaruh Majapahit yang ditemukan pada bangunan Puri ini. Selain itu juga untuk mengetahui apakah pembangunan puri sesuai dengan konsep Sanga Mandala. Metode penelitian dilakukan dengan studi pustaka, dan mendeskripsikan unsur-unsur bangunan Puri yang mendapat pengaruh dari Majapahit, juga melakukan wawancara terhadap narasumber. Dari penelitian ini diketahui bahwa pembangunan Puri menerapkan konsep Sanga Mandala, namun telah mengalami pengembangan sesuai kebutuhan. Pengaruh Majapahit yang ditemukan pada bangunan Puri Kaba Kaba antara lain adalah gapura candi bentar dan paduraksa, arca-arca bergaya tantris, arca kura-kura dan naga, serta arca tokoh berwajah orang asing. Kata Kunci: Pengaruh, Majapahit, Puri Gede Kaba-Kaba